2016
DOI: 10.1126/science.aaf1399
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Cycling Li-O 2 batteries via LiOH formation and decomposition”

Abstract: Liu et al . (Research Article, 30 October 2015, p. 530) described a lithium-oxygen (Li-O 2 ) battery based on lithium iodide (LiI)–assisted lithium hydroxide (LiOH) formation and decomposition. We argue that LiOH cannot be oxidized by triiodide (I 3 – ). The charge capacity is from the oxidation of I – instead of LiOH. The limited-capacity cycling test is misleading when the electrolyte contributes consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 7 publications
1
39
1
Order By: Relevance
“…We demonstrate, in contrast to the work of Shen et al, that the chemical reactivity between LiOH and the triiodide ion (I 3 -) to form IO 3 -indicates that LiOH can be removed on charging; the electrodes do not clog, even after multiple cycles, confirming that solid products are reversibly removed.…”
contrasting
confidence: 99%
“…We demonstrate, in contrast to the work of Shen et al, that the chemical reactivity between LiOH and the triiodide ion (I 3 -) to form IO 3 -indicates that LiOH can be removed on charging; the electrodes do not clog, even after multiple cycles, confirming that solid products are reversibly removed.…”
contrasting
confidence: 99%
“…[18b] Shen et al also reported that LiOH cannot be decomposed by I 3 À upon charging. [24] Zhou andc o-workers proposed that H 2 Oc ould reduce the amount of the side reactions catalyzed by LiI. By increasing the alkalinity of the H 2 O-containinge lectrolyte, the number of side reactions could be reduced and Li 2 O 2 formed.…”
Section: Halogen Rm Charmentioning
confidence: 99%
“…The catalytic mechanism of Ru in Li–O 2 batteries operating via LiOH was further investigated by Liu et al With 50 000 ppm H 2 O in a 1 m LiTFSI/DMSO electrolyte, Ru/SP showed that the charge potential decreased to 3.1 V and that LiOH was the only discharge product at 4000–500 000 ppm H 2 O. Note that the decomposition potential of LiOH was generally ≈3.42 V in alkaline solution and 3.82 V in neutral solution in the absence of catalysts . In this system, Ru facilitates LiOH formation by shifting the reaction equilibrium (2Li 2 O 2 + 2H 2 O → 4 LiOH + O 2 ) toward the products.…”
Section: Other Energy Carriersmentioning
confidence: 97%
“…With H 2 O as the dominant proton source, the voltage gap was reduced to 0.2 V with 0.05 m LiI via LiOH formation based on rGO in 0.25 m LiTFSI/DME electrolyte. The possibility of this reaction was disputed, specifically in regard to whether LiOH can be thermodynamically oxidized by triiodide (normalI3) . Shen et al observed that normalI3 ions were not consumed with the significant accumulation of LiOH.…”
Section: Other Energy Carriersmentioning
confidence: 99%